The guaranteed minimum income in Romania - Tool to support resilience to poverty and increase social inclusion & employment among beneficiaries - Cristina Stroe (Journal of Economic and Social Development (Varaždin), 2022)
The guaranteed minimum income GMI is a recognized tool in practice of reducing poverty and its severe and extreme forms among people facing this social risk. In order to ensure the guaranteed minimum income necessary to cover the needs of persons who are at a certain moment unable to ensure a minimum subsistence, a social aid is granted in addition to the monthly net income of the family or the single person. The purpose of this program was to provide some form of social assistance to these people in difficulty, who have very low incomes or even no incomes. The guaranteed minimum income is thus the most important measure taken into action to reduce poverty and social exclusion, which has a major impact on the existence of the most vulnerable people affected by this social risk. On the other hand, the program aims to increase participation of the recipients in the labour market, by containing certain activation components. Over time, it has been proven that these activation elements are not sufficiently stimulating to mobilize beneficiaries of social aid to transition from their social assistance state to labour market participant (with reference to the activable persons, respectively the working-age people with work capacity). For this reason, more acutely, the guaranteed minimum income is increasingly seen as an incentive tool to encourage work among activable recipients. Thus, the program is aimed at stimulation the social aid beneficiaries in their transition into employment and to get out of the social assistance network. In this sense, one solution is to insert more stimulating activation elements in the GMI program, which would support poverty alleviation among these people and families and increase their level of wellbeing. The paper considers an ex-ante evaluation of the introduction in the guaranteed minimum income program of an incentive to work, more active that the present one, and to estimate some effects that this simulation of introducing a pro-active work incentive in the social aid could have in contributing to poverty alleviation.